2022
DOI: 10.3390/ani12111400
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/Calcium–Alginate Encapsulated Flaxseed Oil on Dairy Cattle Diet: In Vitro Fermentation and Fatty Acid Biohydrogenation

Abstract: The aim of this study was to investigate the effect of using chitosan nanoparticles and calcium alginate in the encapsulation of flaxseed oil on the biohydrogenation of unsaturated fatty acids and in vitro fermentation. The experiments were performed in a completely randomized design with 7 treatments. The experimental treatments included: diets without oil additive (control), diet containing 7% flaxseed oil, diet containing 14% flaxseed oil, diet containing 7% oil encapsulated with 500 ppm chitosan nanocapsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 93 publications
1
3
0
Order By: Relevance
“…However, the protected peanut oil may be unattached by rumen microbes due to the exhaustion period to bind with the EDLEPO microcapsule membrane and emulsified layers. Besharati et al (2022) also confirmed the effects of fat coating and the type of microcapsule sources may explain the rumen degradability rates on the substrate, which can be due to differences in the amount of oil released from different microcapsules per unit of time and the total amount of oil released from the microcapsules.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…However, the protected peanut oil may be unattached by rumen microbes due to the exhaustion period to bind with the EDLEPO microcapsule membrane and emulsified layers. Besharati et al (2022) also confirmed the effects of fat coating and the type of microcapsule sources may explain the rumen degradability rates on the substrate, which can be due to differences in the amount of oil released from different microcapsules per unit of time and the total amount of oil released from the microcapsules.…”
Section: Resultssupporting
confidence: 61%
“…Unfortunately, the present study results on degradability and gas production are not coherent with Olfaz et al (2018) findings. However, Besharati et al (2022) reported that the encapsulation of flaxseed oil with calcium alginate increased the dry matter degradability of substrate with a fluctuation effect on gas production during 96 h incubation. Some researchers reported that vegetable oil supplementation in the diet negatively affects rumen fermentation indicating reduced degradability rates and a lower microbial population (Yanza et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Tannins can inhibit methanogens activity directly, limiting the degree of microbial hydrolysis, and indirectly decreasing the H2 availability [ 164 ], although this can reduce fiber digestion. Their ability to modify the ruminal microbiome can result in a reduction in protein degradation, can reduce methanogenesis and inhibit the fatty acids biohydrogenation [ 165 , 166 , 167 ] ( Figure 5 ).…”
Section: Effect Of Tannins On Ruminant Nutritionmentioning
confidence: 99%
“…EOs have a sedative and stimulating effect on animals, as well as a positive effect on their behavior and immune system. Due to their modulating effect on intestinal microbiota, the use of EOs in animal feeding to improve productive performance, health, and nutrient absorption has become fairly common [ 9 , 10 , 11 ]. However, the mechanisms underlying these functions in horse diets have not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%